INFLUENCEANALYSIS OFCAREER DEVELOPMENTAND ORGANIZATIONAL COMMITMENT TOCIVIL SERVICEPERFORMANCETHROUGHJOB SATISFACTIONINEDUCATION ANDTEACHINGMERAUKE REGENCY - Samuel Waas (Universitas Musamus, Merauke, Papua, 2012)
ABSTRACTInfluenceAnalysis ofCareer Developmentand Organizational Commitment toCivil ServicePerformancethroughJob SatisfactioninEducation andTeachingMerauke RegencyThe purpose of this study to analyze the effect of (1) career development, (2) organizational commitment, (3) job satisfaction and (4) the performance of civil servants in public organizations.The research wasconductedin theDepartmentof EducationandTeachingMeraukeRegency. The method usedin the studyis a questionnairecompleted by69respondents(saturated sample). Data were analyzedusingquantitativeanalysis(pathanalysis)totabulatedata andprocessedusing the toolsof SPSSversion17.Results showed that hypothesis 1 is rejected, is a career development does not directly influence employee job satisfaction. Hypothesis 2 is the commitment of employees received a direct influence on job satisfaction. Hypothesis 3 is accepted, is a career development directly affect performance. Hypothesis 4 was rejected, is the commitment of employees not directly influence the performance. Hypothesis 5 is accepted, the employee job satisfaction directly affects the performance of employees. Hypothesis 6 was rejected, is a career development does not affect performance through job satisfaction. Hypothesis 7 is accepted, is the commitment of employees directly affects the performance through job satisfaction.